An Affordable Wager: The Wider Implications of Regulatory Innovations to Address Vulnerability in Online Gambling - Bedford, Kate (Critical Gambling Studies, 2023)
The British government is introducing new regulatory measures to address gambling harm, including affordability checks on online players that rely on cross-operators data sharing. This article seeks to understand these measures, and their limits. Section 1 recaps what we already know about differentiated restrictions on access to gambling, including as manifest in recent state-industry efforts to deploy online gambling technologies to identify and preempt gambling harm. Section 2 summarises agreed and proposed changes to British online gambling regulation since 2019, focusing in depth on affordability checks for players and the related imperative to develop a ‘single customer view’ of play. Section 3 outlines two grounds for concern about the measures, rooted in the industry’s enthusiasm for affordability checks, and ii. the implications for groups of customers who may already be disadvantaged and hyper-surveilled. I raise these concerns in an attempt to identify a way out of an impasse, such that urgent concerns about gambling harm do not translate so readily into regulatory efforts to differentially restrict access to ever-expanding groups of adults considered vulnerable.